СuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(+2) + SO4(-2) + 2Na(+) + 2OH(-) = Cu(OH)2 + 2Na(+) + SO4(-2)
Cu(+2) + 2OH(-) = Cu(OH)2
3KCl + Na3PO4 = 3NaCl + K3PO4
3K(+) + 3Cl(-) + 3Na(+) + PO4(-3) = 3Na(+) + PO4(-3) + 3Cl(-) + 3K(+)
(реакция не идёт)
Al2(SO4)3 + 3BaCl2 = 3BaSO4 + 2AlCl3
2Al(+3) + 3SO4(-2) + 3Ba(+2) + 6Cl(-) = 3BaSO4 + 2Al(+3) + 6Cl(-)
3Ba(+2) + 3SO4(-2) = 3BaSO4
Na2SO3 + H2SO4 = Na2SO4 + SO2 + H2O
2Na(+) + SO3(-2) + 2H(+) + SO4(-2) = 2Na(+) + SO4(-2) + SO2 + H2O
SO3(-2) + 2H(+) = SO2 + H2O
Na2CO3 + H2SO4 = Na2SO4 + CO2 + H2O
2Na(+) + CO3(-2) + 2H(+) + SO4(-2) = 2Na(+) + SO4(-2) + CO2 + H2O
CO3(-2) + 2H(+) = CO2 + H2O
CuSO4 + 2NaOH = Cu(OH)2 + Na2SO4
Cu(+2) + SO4(-2) + 2Na(+) + 2OH(-) = Cu(OH)2 + 2Na(+) + SO4(-2)
Cu(+2) + 2OH(-) = Cu(OH)2
Объяснение:
H2SO4 + 2NaOH = Na2SO4 + 2H2O
2H(+) + SO4(2-) + 2Na(+) + 2OH(-) = 2Na(+) + SO4(2-) + 2H2O
2H(+) + 2OH(-) = 2H2O
FeCl2 + 2NaOH = Fe(OH)2↓ + 2NaCl
Fe(2+) + 2Cl(-)+ 2Na(+) + 2OH(-) = Fe(OH)2↓ + 2Na(+) + 2Cl(-)
Fe(2+) + 2OH(-) = Fe(OH)2↓
CaCO3 + 2HCl = CaCl2 + CO2↑ + H2O
CaCO3 + 2H(+) + 2Cl(-) = Ca(2+) + 2Cl(-) + CO2↑ + H2O
CaCO3 + 2H(+) = Ca(2+) + CO2↑ + H2O
Na2SO3 + 2HCl = 2NaCl + SO2↑ + H2O
2Na(+) + SO3(2-) + 2H(+) + 2Cl(-) = 2Na(+) + 2Cl(-) + SO2↑ + H2O
SO3(2-) + 2H(+) = SO2↑ + H2O
Ca(OH)2 + Na2SiO3 = CaSiO3↓ + 2NaOH
Ca(OH)2 + 2Na(+) + SiO3(2-) = CaSiO3 + 2Na(+) + 2OH(-)
Ca(OH)2+ SiO3(2-) = CaSiO3 + 2OH(-)